(untitled) (REMUNOM, 2024)
This article addresses the efficiency of rights-restricting sentences as an alternative to prison, analyzing the evidence of their compliance in the current legal system. The context in which these sanctions are developed, their purpose and how they can be applied in the specific case is analytically observed. The criminal alternatives provided for in the legislation to the detriment of prison are discussed, contextualizing their application. To this end, an analysis was carried out based on bibliographical, exploratory and descriptive research, based on legislation, doctrine and jurisprudence, aiming to expand research performance to achieve the best results on the proposed topic. It is concluded that restrictive penalties, like the Brazilian penal system, aim to punish crime with the aim of reinserting the convicted person into society, respecting the principle of proportionality. However, there is a lack of a comprehensive system to implement these measures efficiently, making it subjective. Keywords: Private; Substitute; Punitive; Convicted; Resocialization.